Representations of mental health and arts participation in the national and local British press, 2007-2015 - Atanasova, D.; Koteyko, Nelya; Brown, B.; Crawford, Paul (SAGE, 2017)
We analysed news articles published in national and local British newspapers between 2007 and 2015 to understand 1) how mental health and arts participation were framed and 2) how the relationships between participants in arts initiatives were conceptualised. Using corpus-assisted qualitative frame analysis, we identified frames of recovery, stigma and economy. The recovery frame, which emphasised that mental illness can be treated similarly to physical illness, positioned arts participation as a form of therapy that can complement or substitute medication. The stigma frame presented arts participation as a mechanism for challenging social conceptions that mentally ill individuals are incapable of productive work. The economy frame discussed the economic burden of mentally ill individuals and portrayed arts participation as facilitating their return to employment. Using thematic analysis, which paid attention to the representation of social actors, we found that service users were identified as the prime beneficiaries of arts initiatives and arts participation was conceptualised as a way to bring people with mental health issues together. We discuss these findings against existing research on media representations of mental health and the concept of ‘mutual recovery’ and suggest what wider concurrent developments in the areas of mental health and the media may account for the uncovered frames and themes.